Electronic instructional materials and course requirements "Computer science" for specialty: 1-53 01 01 «Automation of technological processes and production» - (:unkn) unknown (BNTU, 2020)
The purpose of the electronic instructional materials and course requirements by the discipline «Computer science» (EIMCR) is to develop theoretical systemic and practical knowledge in different fields of Computer science. Features of structuring and submission of educational material: EIMCR includes the following sections: theoretical, practical, knowledge control, auxiliary. The theoretical section presents lecture material in accordance with the main sections and topics of the syllabus. The practical section of the EIMCR contains materials for conducting practical classes aimed to develop modern computational thinking, basic skills in computing and making decisions in the field of the fundamentals of computer theory and many computer science fields. The knowledge control section of the EIMCR contains: guidelines for the implementation of the control work aimed at developing the skills of independent work on the course under study, developing the skills of selecting, analyzing and writing out the necessary material, as well as the correct execution of the tasks; list of questions for the credit by the discipline. The auxiliary section of the EIMCR contains the following elements of the syllabus: explanatory note; thematic lectures plan; tables of distribution of classroom hours by topics and informational and methodological part. EIMCR contains active links to quickly find the necessary material.